Engineering band edge properties of WO3 with respect to photoelectrochemical water splitting potentials via a generalized doping protocol of first-row transition metal ions - Kalanur, Shankara S.; Noh, Yong Gyu; Seo, Hyungtak (Applied Surface Science, 2020)
The photoelectrochemical (PEC) water splitting efficiency of WO3 is limited because to its wide band gap, which allows limited absorption of incident sunlight and its unsuitable band edge positions with respect to overall water splitting potentials. Therefore, band edge engineering of WO3 is essential for reducing the band gap and altering band edge positions via substitutional doping of metal ions. Hence, we report a facile and generalized protocol for synthesizing first row transition metal ion (V, Cr, Mn, Fe, Co, Ni, Cu and Zn,) -doped WO3 thin films and explore their band-edge and PEC water-splitting properties. The detailed characterization results show that irrespective of the type of dopant, the morphology is found to change upon doping, whereas the crystal phase, crystal facet, band gap, charge-transfer resistance, carrier density, and oxygen vacancy formation depend on the type of dopant. The band-edge positions of doped WO3 are plotted with respect to a reference hydrogen electrode, revealing a reduction and widening of the band gap and an upward and downward shift in conduction and valence band-edge positions induced by dopants. Overall, our results provide valuable insights into fabricating highly engineered WO3 photoanodes for efficient future PEC water-splitting capabilities.
Keywords: Band edge; Defect state; Reconstructive transformation; Tungsten oxide; Water splitting; Band-edge engineering; Defect states; Reconstructive transformation; Tungsten oxide; Water splitting